Real‐world outcomes using PD‐1 antibodies and BRAF + MEK inhibitors for adjuvant melanoma treatment from 39 skin cancer centers in Germany, Austria and Switzerland. (12th December 2022) - Schumann, Katharina; Mauch, Cornelia; Klespe, Kai‐Christian; Loquai, Carmen; Nikfarjam, Ulrike; Schlaak, Max; Akçetin, Larissa; Kölblinger, Peter; Hoellwerth, Magdalena; Meissner, Markus; Mengi, Guelcin; Braun, Andreas Dominik; et al.
Abstract: Background: Programmed death‐1 (PD‐1) antibodies and BRAF + MEK inhibitors are widely used for adjuvant therapy of fully resected high‐risk melanoma. Little is known about treatment efficacy outside of phase III trials. This real‐world study reports on clinical outcomes of modern adjuvant melanoma treatment in specialized skin cancer centers in Germany, Austria and Switzerland. Methods: Multicenter, retrospective study investigating stage III–IV melanoma patients receiving adjuvant nivolumab (NIV), pembrolizumab (PEM) or dabrafenib + trametinib (D + T) between 1/2017 and 10/2021. The primary endpoint was 12‐month recurrence‐free survival (RFS). Further analyses included descriptive and correlative statistics, and a multivariate linear‐regression machine learning model to assess the risk of early melanoma recurrence. Results: In total, 1198 patients from 39 skin cancer centers from Germany, Austria and Switzerland were analysed. The vast majority received anti PD‐1 therapies ( n = 1003). Twelve‐month RFS for anti PD‐1 and BRAF + MEK inhibitor‐treated patients were 78.1% and 86.5%, respectively (hazard ratio [HR] 1.998 [95% CI 1.335–2.991]; p = 0.001). There was no statistically significant difference in overall survival (OS) in anti PD‐1 (95.8%) and BRAF + MEK inhibitor (96.9%) treated patients ( p > 0.05) during the median follow‐up of 17 months. Data indicates that anti PD‐1 treated patients who develop immune‐related adverse events (irAEs) have lower recurrence rates compared to patients with no irAEs (HR 0.578 [95% CI 0.443–0.754], p = 0.001). BRAF mutation status did not affect overall efficacy of anti PD‐1 treatment ( p > 0.05). In both, anti PD‐1 and BRAF + MEK inhibitor treated cohorts, data did not show any difference in 12‐month RFS and 12‐month OS comparing patients receiving total lymph node dissection (TLND) versus sentinel lymph node biopsy only ( p > 0.05). The recurrence prediction model reached high specificity but only low sensitivity with an AUC = 0.65. No new safety signals were detected. Overall, recorded numbers and severity of adverse events were lower than reported in pivotal phase III trials. Conclusions: Despite recent advances in adjuvant melanoma treatment, early recurrence remains a significant clinical challenge. This study shows that TLND does not reduce the risk of early melanoma recurrence and should only be considered in selected patients. Data further highlight that variables collected during clinical routine are unlikely to allow for a clinically relevant prediction of individual recurrence risk.